ASSISTING UNIVERSITY STUDENTS SKILLS DEVELOPMENT THROUGH SELF-DIRECTED AND SELF-ACCESS LEARNING ACTIVITIES - Bánhegyi, Mátyás; Horváth-Csikós, Gabriella; Fajt, Balázs (Tudásmenedzsment, 2024)
This paper explores the potential role of higher education institutions in equipping students with essential skills for their future careers through self-access and self-directed learning activities. The study focuses on a comprehensive student development framework available at Budapest Business University. Through self-access and self-directed learning as well as innovative educational practices and strategies such as peer collaboration, project-based learning, telecollaboration, skills for life, individual learning accounts, language skills for business and upskilling students are provided with dynamic and engaging learning environments that prepare them for the complexities of the global job market. Introducing concrete examples from the Universitys initiatives, the paper illustrates how self-access and self-directed learning activities enhance students business skills development. The study concludes by advocating educational approaches that empower learners to take control of their learning journey, thereby potentially equipping students with lifelong learning skills essential for navigating in todays ever changing world of work.